Single crystal sodium ion battery positive electrode active material, its manufacturing method and applications
Patent Information
- Application Number
- JP2024552325
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-03
- Filing Date
- 2022-03-31
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2042-03-31
AI Technical Summary
【0045】 サンディング法を基にホウ素元素をドーピングすると、大きい単結晶を製造することができ、従来技術において原材料粒子が細すぎ、焼結した材料が非常にふわふわで、比表面積が大きく、正極活物質の電極製造時の圧密密度が低く、電池のサイクル時に正極材料と電解液との間の副反応が多く、ガスが大量に発生し、電池サイクル性能及び安全性能が低くなるという欠点を解消する。本発明は、単結晶正極活物質におけるホウ素元素の含有量を制御することによって、1~30μmレベルの単結晶粒子を調整して製造することができ、これは、安定的な表面性質を有し、電解液との副反応が少なく、ナトリウムイオン電池に用いる場合に、高いグラム比容量を発揮する前提で、高温でのサイクル性能を顕著に向上させることができる。
Smart Images

Figure 2025506998000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of sodium ion batteries, and more particularly to a method for making single crystal sodium ion battery cathode active material. [Background technology]
[0002] Due to the large radius of the sodium ion, the positive electrode active materials available for sodium ion batteries are relatively limited, and currently, the positive electrode active materials for sodium ion batteries that have been shown to have potential applications include three systems: Prussian blue, layered oxides, and polyanions. The layered oxide system with an O3 phase structure is similar to the ternary positive electrode active materials in lithium ion batteries, and has the advantages of high capacity and high compaction density, making it the most promising positive electrode material and is used by sodium ion battery companies both at home and abroad.
[0003] At present, oxide-based sodium ion battery positive electrode active materials are mainly of secondary spherical particle structure. For example, China Patent CN110416521A discloses magnesium-doped sodium ion battery ternary positive electrode material and its preparation method, which includes the following steps: 1) weigh out 112 parts by weight of sodium carbonate, 40-50 parts by weight of nickel monoxide, 54 parts by weight of ferric oxide, 48 parts by weight of manganese monoxide, 0.1-5.6 parts by weight of magnesium oxide, add them to 610 parts by weight of deionized water, and stir to obtain a mixed solution; 2) add the mixed solution obtained in step 1) to a nano ball mill and ball mill for 20-80 minutes, take out the slurry and spray dry it at 80-120°C to obtain a precursor powder; and 3) heat the precursor powder obtained in step 2 to 750-1000°C at 2-5°C / min in air atmosphere, sinter for 9-15 hours, and cool to room temperature to obtain a magnesium-doped sodium ion battery ternary positive electrode material. As shown in FIG. 2 of the patent, the product obtained by the method is fluffy secondary particle spheres, with a secondary particle diameter of about 8 μm and a primary particle diameter of 0.15-0.4 μm. Such a spherical structure is easy to collapse, has a low compaction density and a large specific surface area, and during the battery cycle, there are many side reactions between the positive electrode material and the electrolyte, and a large amount of gas is generated, resulting in poor battery cycle performance and safety performance.
[0004] China Patent CN113471431A states that NaMn 0.5 Ni 0.5 B x A positive electrode material for an O2 sodium ion battery has been disclosed, which has a composite phase of P2 phase and O3 phase and has a relatively dense secondary spherical morphology, and its manufacturing method includes mixing materials containing a sodium source, a manganese source, a nickel source and a boron source in a molar ratio of Na:Mn:Ni:B elements of (1-1.05):0.5:0.5:x to obtain a mixture, and heat treating the mixture at 800-900°C in an oxygen-containing atmosphere to obtain a positive electrode material. The positive electrode material uses O3 phase to improve the P2 phase, and has improved electrochemical performance compared to the P2 phase material, but the method of this patent cannot produce a material with a pure O3 phase, and the corresponding electrochemical performance of the material can be further improved.
[0005] The above-mentioned conventional secondary spherical particle structure has several problems: 1. The mechanical strength of the particle structure is low, and the secondary spheres are easily broken during the process of compressing the pole pieces, which affects the compaction density and cycle performance of the pole pieces; 2. The active material has a large contact surface area with the electrolyte, which causes many side reactions when in contact with the electrolyte, which affects the cycle performance and safety performance.
[0006] In this regard, engineers have been trying to prepare oxide-based sodium ion battery positive electrode active materials in single crystal form. For example, Chinese Patent CN109817970A describes a method of mixing an aqueous mixture of iron salt, manganese salt and M salt, a precipitant, a complexing agent and a dispersing agent, reacting the mixture with each other, obtaining a solid as a battery electrode material precursor, mixing the precursor with sodium salt, sintering, and cooling. Instead, a single crystal sodium ion battery electrode material is obtained, and a method for producing the single crystal sodium ion battery electrode material is disclosed, in which the dispersant is ammonium polyacrylate. In such a method, in the large-scale production process, the solubility product constant of the iron salt is too low, and it is easy to precipitate before other metals, and the coprecipitated substances are distributed unevenly, which directly affects the electrochemical performance. Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention aims to provide a method for producing a single-crystal sodium ion battery positive electrode active material, which can stably produce a single-crystal sodium ion battery positive electrode active material having a high compaction density, a small specific surface area, and excellent electrochemical performance on a large scale, in view of the shortcomings and deficiencies of the prior art. [Means for solving the problem]
[0008] In order to solve the above technical problems, the technical solutions adopted by the present invention are as follows:
[0009] A method for producing a single crystal sodium ion battery positive electrode active material, the single crystal sodium ion battery positive electrode active material containing elements of sodium, M metal, boron and oxygen, the method including the steps of: adding water to an M element-containing compound, a boron element-containing compound and a sodium source, preparing a slurry, and sanding the slurry to obtain a mixed slurry; and spray-drying and sintering the mixed slurry to obtain the single crystal sodium ion battery positive electrode active material.
[0010] According to some preferred embodiments of the present invention, the chemical formula of the single crystal sodium ion battery cathode active material is: x M y B z O2, where M is one or more combinations selected from Li, Mg, Al, Si, K, Ca, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Sr, Y, Zr, Nb, Mo, Ru, In, Sn, Sb, W, Ta, Ba, Bi, La, Ce, and Eu, and 0.80≦x≦1.40, 0.6≦y≦0.9999, and 0.0001≦z≦0.4.
[0011] Preferably, the formula Na x M y B z In O2, 0.95≦x≦1.05, 0.8≦y≦0.9999, and 0.0001≦z≦0.2.
[0012] More preferably, the formula Na x M y B z In O2, 0.98≦x≦1.04, 0.9≦y≦0.9999, and 0.0001≦z≦0.1.
[0013] In some specific embodiments of the present invention, M is selected from one or more combinations of Fe, Ni, Mn, Cu, and Ti.
[0014] In some specific embodiments of the present invention, the M element-containing compound is selected from one or more combinations of oxides, hydroxides, carbonates, oxalates, and nitrates of the M element.
[0015] Further, the M element-containing compound is selected from one or more combinations of nickel manganese hydroxide, ferric oxide, titanium dioxide, nickel oxide, and manganese dioxide.
[0016] In some specific embodiments of the present invention, the boron-containing compound is selected from one or more combinations of boron oxide, boric acid, borate salts, borohydride salts, boron trihalides, trifluoroboric acid, borate esters, boranes, and metal borides.
[0017] Further, the boron-containing compound is selected from the group consisting of boric acid, boron oxide, and a combination of two of them.
[0018] In some specific embodiments of the invention, the sodium source is selected from one or more combinations of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium oxide, sodium peroxide, sodium nitrate, sodium acetate, and sodium oxalate.
[0019] Further, the sodium source is selected from one or more combinations of sodium carbonate, sodium bicarbonate, and sodium hydroxide.
[0020] In some specific embodiments of the present invention, the molar ratio of the M element-containing compound, the boron element-containing compound, and the sodium source is (0.6-0.9999):(0.4-0.0001):(0.80-1.40).
[0021] More preferably, the molar ratio of the M element-containing compound, the boron element-containing compound and the sodium source is (0.9 to 0.9999):(0.1 to 0.0001):(0.90 to 1.10).
[0022] Further, the molar ratio of the M element-containing compound, the boron element-containing compound and the sodium source is 0.95:0.05:1.0.
[0023] In some specific embodiments of the present invention, the sanding time is 0.6 to 7.8 hours.
[0024] Furthermore, the sanding time is 1 to 4 hours.
[0025] In some specific embodiments of the present invention, the abrasives of the sanding are zirconia balls having a particle size of 0.1 to 0.8 mm.
[0026] In some specific embodiments of the present invention, the sanding speed is 800 to 3000 rpm.
[0027] Furthermore, the sanding speed is 1500 to 2500 rpm.
[0028] In some specific embodiments of the present invention, the solid content of the mixed slurry is 10% to 60%.
[0029] Furthermore, the mixed slurry has a solid content of 20 to 40%.
[0030] In some specific embodiments of the present invention, the median particle size of the particles in the mixed slurry is 20 to 800 nm.
[0031] In some specific embodiments of the present invention, the mixed slurry is ground after sintering.
[0032] Furthermore, in the case of the spray drying, the rotation speed of the atomizer disk is 1000 to 3000 rpm, the intake air temperature is 150 to 300°C, and the blown air temperature is 80 to 120°C.
[0033] In some specific embodiments of the present invention, the sintering is carried out in air, and the sintering is carried out at a temperature of 750 to 1100° C. for a time of 5 to 25 hours.
[0034] Furthermore, the sintering is carried out at a temperature of 850 to 1000° C. for a time of 8 to 16 hours.
[0035] In the manufacturing method of the present invention, during the preparation of the mixed slurry, sanding is used to process water-soluble substances, which can realize uniform mixing at the molecular level; water-insoluble raw materials can be processed to realize uniform mixing of insoluble substances at the nano level; and the water-soluble raw materials and water-insoluble raw materials can be processed to uniformly mix at the nano level. Sanding ensures uniform mixing of raw materials at the nano level, and can stably obtain a positive electrode material with excellent electrochemical activity during high-temperature sintering. In addition, by adding a boron element-containing compound to the raw materials, the nano-level primary particles can be rapidly melted and bonded during high-temperature sintering, and a single-crystal sodium ion battery positive electrode active material of about 1 to 30 μm can be sintered, and the material is not fluffy, so it has a high compaction density and can greatly reduce the side reaction between the positive electrode material and the electrolyte. And, by adjusting the content of boron element in the single-crystal positive electrode active material, the particle size of the single-crystal particles of the positive electrode active material can be controlled. There is also a synergistic effect between the sanding method and the addition of the boron element-containing compound, and both are essential for the manufacture of a perfect single crystal positive electrode active material.
[0036] In addition, the present invention can perform spray drying on the mixed slurry, and the spray drying method can maintain the uniform distribution of various raw materials in the drying process of the uniformly mixed slurry, and ensure that the various raw materials do not separate during the molding process.
[0037] The present invention is characterized in that the micromorphology exhibits a single crystal structure and the average grain size D 50 is 1-30μm, and compaction density is 2.8-3.6g / cm 3 , specific surface area is 0.2 to 1.0 m 2The present invention further provides a single crystal sodium ion battery positive electrode active material produced by the above method, wherein the positive electrode active material has a viscosity of 1000:1 or more.
[0038] The present invention further provides the use of the single crystal sodium ion battery positive electrode active material in a sodium ion battery positive electrode.
[0039] When the single crystal sodium ion battery positive electrode active material is applied to a sodium ion battery positive electrode, the obtained sodium ion battery has an initial gram capacity of 123-130mAh / g at 0.1C, 25°C, a gram capacity after 1 cycle of 117-127mAh / g at 1C, 60°C, and a gram capacity after 100 cycles of 1C, 60°C of 100-120mAh / g, i.e., a cycle retention rate after 100 cycles at a high temperature of 60°C of 84%-92%.
[0040] The present invention further provides a sodium ion battery positive electrode material, comprising a positive electrode active material including the single crystal sodium ion battery positive electrode active material, an adhesive, and a conductive agent.
[0041] The present invention further provides a sodium ion battery cathode made from said sodium ion battery cathode material.
[0042] The present invention further provides a sodium ion battery comprising a positive electrode comprising the sodium ion battery positive electrode.
[0043] Compared with the prior art, the present invention has the following technical advantages:
[0044] The manufacturing method of the present invention can be applied to a wide variety of raw materials and can efficiently realize uniform mixing of various raw materials at the nano level, and the mixed slurry can form a perfect layered O3 phase structure after sintering.
[0045] Doping with boron element based on sanding method can produce large single crystals, which solves the shortcomings of the prior art, such as raw material particles being too fine, sintered materials being very fluffy, large specific surface area, low compaction density during electrode production of positive electrode active material, many side reactions between the positive electrode material and electrolyte during battery cycle, large amount of gas generation, and poor battery cycle performance and safety performance. The present invention can adjust and produce single crystal particles of 1-30 μm level by controlling the content of boron element in the single crystal positive electrode active material, which has stable surface properties, few side reactions with electrolyte, and can significantly improve cycle performance at high temperature under the premise of high gram specific capacity when used in sodium ion batteries. [Brief description of the drawings]
[0046] [Figure 1] 1 is a scanning electron microscope photograph of NaNi0.32Fe0.33Mn0.32B0.03O2 produced in Example 1. [Diagram 2] FIG. 2 is an XRD diagram of NaNi0.32Fe0.33Mn0.32B0.03O2 produced in Example 1. [Diagram 3] FIG. 2 is a charge / discharge curve diagram of NaNi0.32Fe0.33Mn0.32B0.03O2 produced in Example 1. [Figure 4] 1 is a scanning electron microscope photograph of NaNi0.31Fe0.33Mn0.31B0.05O2 produced in Example 2. [Diagram 5] FIG. 2 is an XRD diagram of NaNi0.31Fe0.33Mn0.31B0.05O2 produced in Example 2. [Figure 6] FIG. 2 is a charge / discharge curve diagram of NaNi0.31Fe0.33Mn0.31B0.05O2 produced in Example 2. [Figure 7] 1 is a cycle diagram of NaNi0.31Fe0.33Mn0.31B0.05O2 produced in Example 2 at 2.0 to 4.0 V / 1C at high temperature (60°C). [Figure 8]1 is a scanning electron microscope photograph of NaNi0.25Fe0.40Mn0.25Ti0.05B0.05O2 produced in Example 4. [Figure 9] FIG. 1 is an XRD diagram of NaNi0.25Fe0.40Mn0.25Ti0.05B0.05O2 produced in Example 4. [Figure 10] FIG. 1 is a charge / discharge curve diagram of NaNi0.25Fe0.40Mn0.25Ti0.05B0.05O2 produced in Example 4. [Figure 11] 1 is a cycle diagram of NaNi0.25Fe0.40Mn0.25Ti0.05B0.05O2 produced in Example 4 at 2.0 to 4.0V / 1C at high temperature (60°C). [Figure 12] 1 is a scanning electron microscope photograph of NaNi1 / 3Fe1 / 3Mn1 / 3O2 produced in Comparative Example 1. [Figure 13] FIG. 1 is an XRD diagram of NaNi1 / 3Fe1 / 3Mn1 / 3O2 produced in Comparative Example 1. [Figure 14] FIG. 2 is a charge / discharge curve diagram of NaNi1 / 3Fe1 / 3Mn1 / 3O2 produced in Comparative Example 1. [Figure 15] 1 is a cycle diagram of NaNi1 / 3Fe1 / 3Mn1 / 3O2 produced in Comparative Example 1 at 2.0 to 4.0 V / 1C at high temperature (60° C.). [Figure 16] 1 is a scanning electron microscope photograph of NaNi0.32Fe0.33Mn0.32B0.03O2 produced in Comparative Example 2. [Figure 17] FIG. 2 is an XRD diagram of NaNi0.32Fe0.33Mn0.32B0.03O2 produced in Comparative Example 2. [Figure 18] FIG. 2 is a charge / discharge curve diagram of NaNi0.32Fe0.33Mn0.32B0.03O2 produced in Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0047] In order to better understand the contents of the present invention, the present invention will be further described with reference to specific examples and drawings. It should be understood that these examples are merely for the purpose of further illustrating the invention, and do not limit the scope of the present invention. It should also be understood that after reading the contents of the present invention, any slight improvements or adjustments made by those skilled in the art to the present invention without departing from the principles of the present invention are also included in the scope of protection of the present invention. Unless otherwise specified below, all raw materials are commercially available.
[0048] In the following examples and comparative examples, the charge / discharge curve and high-temperature cycle performance tests are performed using the following method. First, in the manufacture of a sodium ion battery, 20 g of the prepared positive electrode active material was weighed out, 0.64 g of conductive agent SP and 0.64 g of PVDF dissolved in NMP were added, and the mixture was mixed uniformly, and then coated on aluminum foil to manufacture an electrode sheet. In a glove box in an argon atmosphere, a button battery was assembled using metallic sodium flakes as the negative electrode, Celgard2700 as the diaphragm, and 1 mol / L NaPF6+EC:DEC(1:1)+5%FEC as the electrolyte. Then, the charge / discharge curve was tested under the conditions of a voltage range of 2.0-4.0 V, a charge / discharge ratio of 0.1 C, a current of 13 mA, and a test temperature of 25±2° C., and the cycle performance was tested by cycling 100 times under the conditions of a voltage range of 2.0-4.0 V, a charge / discharge ratio of 1 C, a current of 130 mA, and 60° C.
[0049] Example 1 In this embodiment, the chemical formula is NaNi 0.32 Fe 0.33 Mn 0.32 B 0.03 The present invention provides a sodium ion battery positive electrode active material, which is O2, and the manufacturing method thereof is as follows: (1) 3.2 mol of Ni 0.5 Mn 0.5 taking (OH)2, 0.825 mol Fe2O3, 0.15 mol H3BO3, 2.5 mol Na2CO3 and adding all the raw materials to 3.5 L of water to prepare a slurry; (2) adding the slurry obtained in step (1) to a sand mill and grinding for 3 hours, the grinding bodies are zirconia balls with a particle size of 0.2 mm, the sanding rotation speed is 2500 rpm, and grinding is performed to obtain a mixed slurry with an average particle size of about 350 nm; (3) transferring the mixed slurry produced in step (2) into a mixing drum, thoroughly stirring, adding pure water to prepare a slurry with a solid content of 30±1%, spray drying under the conditions of an atomization frequency of the spray drying machine of 35Hz, an intake air temperature of 190°C, and a blowing air temperature of 85°C; sintering the dried product at 850-1000°C in an atmospheric furnace for 12 hours, cooling to 80°C or less, jaw crushing, roller pairing, and pulverizing to obtain a sodium ion battery positive electrode active material (sample name is NFM-B1).
[0050] A scanning electron micrograph of NFM-B1 is shown in FIG. 1, which shows that the material is in single crystal form. The XRD of NFM-B1 is shown in FIG. 2, which shows that the material is an α-NaFeO2 type pure phase layered structure. The charge-discharge curve diagram of NFM-B1 is shown in FIG. 3, which shows that the discharge specific capacity is 128.8 mAh / g at 0.1 C magnification within the voltage window of 2.0-4.0 V.
[0051] Example 2 In this embodiment, the chemical formula is NaNi 0.31 Fe 0.33 Mn 0.31 B 0.05 The present invention provides a sodium ion battery positive electrode active material, which is O2, and the manufacturing method thereof is as follows: (1) 3.1 mol of Ni 0.5 Mn 0.5 taking (OH)2, 0.825 mol Fe2O3, 0.25 mol H3BO3, 2.5 mol Na2CO3 and adding all the raw materials to 3.5 L of water to prepare a slurry; (2) adding the slurry obtained in step (1) to a sand mill and grinding for 3 hours, the grinding bodies are zirconia balls with a particle size of 0.2 mm, the sanding rotation speed is 2500 rpm, and grinding is performed to obtain a mixed slurry with an average particle size of about 350 nm; (3) transferring the mixed slurry produced in step (2) to a mixing drum, thoroughly stirring, adding pure water to prepare a slurry with a solid content of 30±1%, spray drying under the conditions of an atomization frequency of the spray drying machine of 35Hz, an intake air temperature of 190°C, and a blowing air temperature of 85°C; sintering the dried product at 850-1000°C in an atmospheric furnace for 12 hours, cooling to 80°C or less, jaw crushing, roller pairing, and pulverizing to obtain a sodium ion battery positive electrode active material (sample name is NFM-B2).
[0052] A scanning electron micrograph of NFM-B2 is shown in FIG. 4, showing that the material is in single crystal form. The XRD of NFM-B2 is shown in FIG. 5, showing that the material is in α-NaFeO2 type pure phase layered structure. The charge-discharge curve diagram of NFM-B2 is shown in FIG. 6, showing that the discharge specific capacity is 129.1 mAh / g at 0.1 C magnification within the voltage window of 2.0-4.0 V. The high temperature cycle diagram of NFM-B2 is shown in FIG. 7, showing that the capacity retention is 90.9% after 100 cycles at 60°C, 1 C magnification within the voltage window of 2.0-4.0 V.
[0053] Example 3 In this embodiment, the chemical formula is NaNi 0.31 Fe 0.33 Mn 0.31 B 0.05 The present invention provides a sodium ion battery positive electrode active material, which is O2, and the manufacturing method thereof is as follows: (1) taking 1.55 mol NiO, 1.55 mol MnO2, 0.825 mol Fe2O3, 0.25 mol H3BO3, 2.5 mol Na2CO3, and adding all the raw materials to 3.5 L of water to prepare a slurry; (2) adding the slurry obtained in step (1) to a sand mill and grinding for 3 hours, the grinding bodies are zirconia balls with a particle size of 0.2 mm, the sanding rotation speed is 2500 rpm, and grinding is performed to obtain a mixed slurry with an average particle size of about 350 nm; (3) transferring the mixed slurry produced in step (2) to a mixing drum, thoroughly stirring, adding pure water to prepare a slurry with a solid content of 30±1%, spray drying under the conditions of an atomization frequency of the spray drying machine of 35Hz, an intake air temperature of 190°C, and a blowing air temperature of 85°C; sintering the dried product at 850-1000°C in an atmospheric furnace for 12 hours, cooling to 80°C or less, jaw crushing, roller pairing, and pulverizing to obtain a sodium ion battery positive electrode active material (sample name is NFM-B3).
[0054] Example 4 In this embodiment, the chemical formula is NaNi 0.25 Fe 0.40 Mn 0.25 Ti 0.05 B 0.05 The present invention provides a sodium ion battery positive electrode active material, which is O2, and the manufacturing method thereof is as follows: (1) 2.5 mol of Ni 0.5 Mn 0.5 Taking (OH)2, 1 mol Fe2O3, 0.25 mol TiO2, 0.25 mol H3BO3, 2.5 mol Na2CO3 and adding all the raw materials to 3.5 L of water to prepare a slurry; (2) adding the slurry obtained in step (1) to a sand mill and grinding for 3 hours, the grinding bodies are zirconia balls with a particle size of 0.2 mm, the sanding rotation speed is 2500 rpm, and grinding is performed to obtain a mixed slurry with an average particle size of about 350 nm; (3) transferring the mixed slurry produced in step (2) to a mixing drum, thoroughly stirring, adding pure water to prepare a slurry with a solid content of 30±1%, spray drying under the conditions of an atomization frequency of the spray drying machine of 35Hz, an intake air temperature of 190°C, and an outlet air temperature of 85°C; sintering the dried product at 850-1000°C in an atmospheric furnace for 12 hours, cooling to below 80°C, jaw crushing, roller pairing, and pulverizing to obtain a sodium ion battery positive electrode active material, the sample name of which is NFM-B3.
[0055] The scanning electron micrograph of NFM-TB1 is shown in FIG. 8, which shows that the material is in single crystal form. The TB1 of NFM-B2 is shown in FIG. 9, which shows that the material is in α-NaFeO2 type pure phase layered structure. The charge-discharge curve of NFM-TB1 is shown in FIG. 10, which shows that the material is in single crystal form. It can be seen that the discharge specific capacity is 124.8mAh / g at 0.1C magnification within the voltage window of 0.0-4.0V. The high temperature cycling diagram of NFM-B2 is shown in Figure 7, which shows that the capacity retention is 90.9% after 100 cycles at 60°C, 1C magnification within the voltage window of 2.0-4.0V.
[0056] Example 5 In this embodiment, the chemical formula is NaNi 0.25 Fe 0.40 Mn 0.25 Ti 0.05 B 0.05 The present invention provides a sodium ion battery positive electrode active material, which is O2, and the manufacturing method thereof is as follows: (1) taking 1.25 mol NiO, 1.25 mol MnO2, 1 mol Fe2O3, 0.25 mol TiO2, 0.25 mol H3BO3, 2.5 mol Na2CO3, and adding all the raw materials to 3.5 L of water to prepare a slurry; (2) adding the slurry obtained in step (1) to a sand mill and grinding for 3 hours, the grinding bodies are zirconia balls with a particle size of 0.2 mm, the sanding rotation speed is 2500 rpm, and grinding is performed to obtain a mixed slurry with an average particle size of about 350 nm; (3) transferring the mixed slurry produced in step (2) into a mixing drum, thoroughly stirring, adding pure water to prepare a slurry with a solid content of 30±1%, spray drying under the conditions of an atomization frequency of the spray drying machine of 35Hz, an intake air temperature of 190°C, and a blowing air temperature of 85°C; sintering the dried product at 850-1000°C in an atmospheric furnace for 12 hours, cooling to 80°C or less, jaw crushing, roller pairing, and pulverizing to obtain a sodium ion battery positive electrode active material (sample name is NFM-B3).
[0057] Example 6 In this embodiment, the chemical formula is NaNi 0.25 Fe 0.40 Mn 0.30 B 0.05 The present invention provides a sodium ion battery positive electrode active material, which is O2, and the manufacturing method thereof is as follows: (1) taking 1.25 mol NiO, 1.50 mol MnO2, 1 mol Fe2O3, 0.25 mol H3BO3, 2.5 mol Na2CO3, and adding all the raw materials to 3.5 L of water to prepare a slurry; (2) adding the slurry obtained in step (1) to a sand mill and grinding for 3 hours, the grinding bodies are zirconia balls with a particle size of 0.2 mm, the sanding rotation speed is 2500 rpm, and grinding is performed to obtain a mixed slurry with an average particle size of about 350 nm; (3) transferring the mixed slurry produced in step (2) to a mixing drum, thoroughly stirring, adding pure water to prepare a slurry with a solid content of 30±1%, spray drying under the conditions of an atomization frequency of the spray drying machine of 35Hz, an intake air temperature of 190°C, and a blowing air temperature of 85°C; sintering the dried product at 850-1000°C in an atmospheric furnace for 12 hours, cooling to 80°C or less, jaw crushing, roller pairing, and pulverizing to obtain a sodium ion battery positive electrode active material (sample name is NFM-B3).
[0058] Comparative Example 1 In this embodiment, the chemical formula is NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 The present invention provides a sodium ion battery positive electrode active material, which is O2, and the manufacturing method thereof is as follows: (1) 3.33 mol of Ni 0.5 Mn 0.5 Taking (OH)2, 0.835 mol of Fe2O3, 2.5 mol of Na2CO3 and adding all the raw materials to 3.5 L of water to prepare a slurry; (2) adding the slurry obtained in step (1) to a sand mill and grinding for 3 hours, the grinding bodies are zirconia balls with a particle size of 0.2 mm, the sanding rotation speed is 2500 rpm, and grinding is performed to obtain a mixed slurry with an average particle size of about 350 nm; (3) The mixed slurry produced in step (2) is transferred to a mixing drum, thoroughly stirred, and pure water is added to prepare a slurry with a solid content of 30±1%, which is spray-dried under the conditions of an atomization frequency of 35Hz, an intake air temperature of 190°C, and an outlet air temperature of 85°C. The dried product is sintered in an atmospheric furnace at 850-1000°C for 12 hours, and then cooled to 80°C or less. cooling, jaw crushing, roller paring and grinding to obtain a sodium ion battery positive electrode active material (sample name is NFM-1).
[0059] A scanning electron microscope photograph of NFM-1 is shown in FIG. 12, which shows that the material is a fluffy secondary particle sphere, with the primary particles within the sphere being about 0.5 μm. The XRD of NFM-1 is shown in FIG. 13, which shows that the material is an α-NaFeO2 type pure phase layered structure. The charge / discharge curve diagram of NFM-1 is shown in FIG. 14, which shows that the discharge specific capacity is 125.0 mAh / g at 0.1 C magnification within a voltage window of 2.0-4.0 V. The high temperature cycle diagram of NFM-1 is shown in FIG. 15, which shows that the capacity retention is 83% after 100 cycles at 60°C, 1 C magnification within a voltage window of 2.0-4.0 V.
[0060] Comparative Example 2 In this embodiment, the chemical formula is NaNi 0.32 Fe 0.33 Mn 0.32 B 0.03 The present invention provides a sodium ion battery positive electrode active material, which is O2, and the manufacturing method thereof is as follows: (1) adding nickel sulfate, ferrous sulfate, and manganese sulfate in a Ni:Fe:Mn molar ratio of 1:1:1 to pure water to prepare a solution having a total concentration of metal elements of 1.3 mol / L; (2) preparing a 4.0 mol / L sodium hydroxide solution and a 5.0 mol / L ammonia solution; (3) adding the metal salt solution obtained in step (1), the sodium hydroxide solution obtained in step (2), and the ammonia solution obtained in step (2) to the reactor at rates of 2.5 L / h, 1.5 L / h, and 0.2 L / h, respectively, and reacting them for 12 hours at a reaction temperature of 50° C., a reaction pH of 11.5, and a stirring speed of 650 rpm to produce a precursor; (4) The above precursor is washed with pure water, filtered, dried, and then Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 obtaining (OH)2; (5) mixing the precursor, boric acid and sodium carbonate in a molar ratio of the total amount of metal elements in the precursor, boron, and sodium element in the sodium carbonate of 0.97:0.03:1, polishing the mixture, sintering the mixture at 850-1000°C for 12 hours in an atmospheric furnace, cooling the mixture to 80°C or less, jaw crushing, roller pairing, and pulverizing the mixture to obtain a sodium ion battery positive electrode active material (sample name is NFM-B5).
[0061] In this manufacturing method, water is not added when grinding the precursor, the precursor is not prepared in the form of a mixed slurry, and spray drying is not performed before sintering.
[0062] The scanning electron micrograph of NFM-B5 is shown in FIG. 16, which shows that the material has an irregular quasi-single crystal structure. The XRD of NFM-B5 is shown in FIG. 17, which shows that the material has a composite phase structure of P2 and O3. The charge-discharge curve diagram of NFM-1 is shown in FIG. 18, which shows that the discharge specific capacity is 125.0 mAh / g at 0.1 C magnification within the voltage window of 2.0-4.0 V.
[0063] Performance Testing The positive electrode active materials prepared in Examples 1 to 6 and Comparative Examples 1 to 2 were subjected to physical and chemical performance tests, and the results of the physical and chemical performance are shown in Table 1 below.
[0064] [Table 1]
[0065] The positive electrode active materials prepared in the above Examples 1 to 6 and Comparative Examples 1 to 2 were used in the sodium ion battery performance test. The sodium ion battery was prepared by weighing out 20 g of the positive electrode active material, adding 0.64 g of conductive agent SP and 0.64 g of PVDF dissolved in NMP, mixing uniformly, and then coating the aluminum foil to prepare an electrode sheet. In a glove box under an argon atmosphere, a button battery was assembled using metallic sodium flakes as the negative electrode, Celgard2700 as the diaphragm, and 1 mol / L NaPF6+EC:DEC(1:1)+5%FEC as the electrolyte. The test voltage section was 2.0 to 4.0 V, and the 0.1C current was 13 mA. The test results are shown in Table 2 below.
[0066] [Table 2]
[0067] As can be seen from Tables 1 and 2 above, in the present invention, water is added during grinding of the precursor to prepare a mixed slurry, and spray drying is performed before sintering, and a boron-containing compound is added to the raw materials, thereby realizing the positive active material to form a perfect layered single crystal structure, and the single crystal particles grow large and densely, which significantly improves the compaction density of the positive active material and reduces the specific surface area. When the positive active material is used in a sodium ion battery, it can ensure that the cycle performance at high temperature is significantly improved under the premise of exerting a high gram-specific capacity.
[0068] The above examples are only intended to explain the technical ideas and features of the present invention, and the purpose thereof is to enable people familiar with the art to understand the contents of the present invention and to practice the same based on the contents. They do not limit the scope of protection of the present invention, and any equivalent changes or modifications substantially made based on the spirit of the present invention shall be included in the scope of protection of the present invention.
Claims
1. 1. A method for producing a single crystal sodium ion battery cathode active material comprising the elements sodium, M metal, boron and oxygen, comprising: The manufacturing method includes a step of adding water to an M element-containing compound, a boron element-containing compound, and a sodium source to prepare a slurry, and a step of sanding the slurry to obtain a mixed slurry; and a step of spray-drying and sintering the mixed slurry to obtain the single crystal sodium ion battery positive electrode active material. The present invention relates to a method for producing a single crystal sodium ion battery positive electrode active material.
2. The chemical formula of the single crystal sodium ion battery positive electrode active material is Na x M y B z O 2 where M is one or a combination of one or more selected from Li, Mg, Al, Si, K, Ca, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Sr, Y, Zr, Nb, Mo, Ru, In, Sn, Sb, W, Ta, Ba, Bi, La, Ce, and Eu, and 0.80≦x≦1.40, 0.6≦y≦0.9999, and 0.0001≦z≦0.
4. The method according to claim 1 .
3. The M element-containing compound is selected from one or more combinations of oxides, hydroxides, carbonates, oxalates, and nitrates of the M element. The method according to claim 1 .
4. The boron-containing compound is selected from one or more combinations of boron oxide, boric acid, borate salts, borohydride salts, boron trihalides, trifluoroboric acid, borate esters, boranes, and metal borides. The method according to claim 1 .
5. The sodium source is selected from one or more combinations of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium oxide, sodium peroxide, sodium nitrate, sodium acetate, and sodium oxalate. The method according to claim 1 .
6. The molar ratio of the M element-containing compound, the boron element-containing compound and the sodium source is (0.6 to 0.9999):(0.4 to 0.0001):(0.80 to 1.40). The method according to claim 1 .
7. The sanding time is 0.6 to 7.8 hours, and / or the abrasives of the sanding are zirconia balls with a particle size of 0.1 to 0.8 mm, and / or the sanding speed is 800 to 3000 rpm. The method according to claim 1 .
8. The mixed slurry has a solid content of 10% to 60% and / or the median particle size of the particles in the mixed slurry is 20 to 800 nm. The method according to claim 1 .
9. In the case of the spray drying, the rotation speed of the atomizer disk is 1000 to 3000 rpm, the intake air temperature is 150 to 300° C., and the blown air temperature is 80 to 120° C. The method according to claim 1 .
10. The sintering is performed in air, the sintering temperature is 750-1100° C., the sintering time is 5-25 hours, and / or the mixed slurry is pulverized after sintering. The method according to claim 1 .
11. A single crystal sodium ion battery positive electrode active material produced by the method according to any one of claims 1 to 10, The micromorphology of the single crystal sodium ion battery positive electrode active material exhibits a single crystal structure, and the average particle size D 50 is 1 to 30 μm, and the compaction density is 2.8 to 3.6 g / cm 3 and the specific surface area is 0.2 to 1.0 m 2 / g A single crystal sodium ion battery positive electrode active material.
12. Use of the single crystal sodium ion battery positive electrode active material according to claim 11 in a sodium ion battery positive electrode.
13. A sodium ion battery positive electrode material comprising a positive electrode active material, an adhesive, and a conductive agent, The positive electrode active material comprises the single crystal sodium ion battery positive electrode active material according to claim 11. A sodium ion battery positive electrode material characterized by:
14. 1. A sodium ion battery positive electrode, comprising: The sodium ion battery positive electrode is made from the sodium ion battery positive electrode material according to claim 13. A sodium ion battery positive electrode comprising:
15. 1. A sodium ion battery comprising a positive electrode, The positive electrode comprises a sodium ion battery positive electrode according to claim 14. A sodium ion battery characterized by:
Citation Information
Patent Citations
Methods for preparing nickel-cobalt-manganese ternary positive electrode material with large single crystal morphology and precursor thereof
CN111943279A
Sodium-lithium-iron-manganese-based layered oxide material, and preparation method and application thereof
CN113078299A
Layer structured oxide and secondary battery
JP1996055624A